2021
DOI: 10.1038/s41598-021-91335-8
|View full text |Cite
|
Sign up to set email alerts
|

A small RNA regulates pprM, a modulator of pleiotropic proteins promoting DNA repair, in Deinococcus radiodurans under ionizing radiation

Abstract: Networks of transcriptional and post-transcriptional regulators are critical for bacterial survival and adaptation to environmental stressors. While transcriptional regulators provide rapid activation and/or repression of a wide-network of genes, post-transcriptional regulators, such as small RNAs (sRNAs), are also important to fine-tune gene expression. However, the mechanisms of sRNAs remain poorly understood, especially in less-studied bacteria. Deinococcus radiodurans is a gram-positive bacterium resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
(107 reference statements)
1
14
0
Order By: Relevance
“…According to published literature, numerous antioxidant proteins, e.g., superoxide dismutase (SOD), OxyR, PerR, DdrI, and PprI, as well as various antioxidant metabolites against ROS and PC, help to enhance protection of the proteome of D. radiodurans ( 50 ). Moreover, some studies showed that many small RNAs also play essential roles in the transport of antioxidant proteins and regulation of manganese and DNA repair systems in D. radiodurans ( 73 , 74 ). Some proteins reduced the effect of oxidized RNA, which also helped protect cells from oxidative stress ( 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to published literature, numerous antioxidant proteins, e.g., superoxide dismutase (SOD), OxyR, PerR, DdrI, and PprI, as well as various antioxidant metabolites against ROS and PC, help to enhance protection of the proteome of D. radiodurans ( 50 ). Moreover, some studies showed that many small RNAs also play essential roles in the transport of antioxidant proteins and regulation of manganese and DNA repair systems in D. radiodurans ( 73 , 74 ). Some proteins reduced the effect of oxidized RNA, which also helped protect cells from oxidative stress ( 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past, extensive studies have been conducted to understand the mechanism of the resistance of D. radiodurans to oxidative stresses, most of which mainly focused on gene regulation, protein functions, and sRNA regulations ( 38 , 39 , 46 , 50 52 ). Our previous work has revealed that ionizing radiation can cause a significantly increased 8-oxoG-RNA concentration in D. radiodurans ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and preparation were done immediately as described above. Densitometry with ImageJ was used to measure density counts in lane measurements, and compare density using integrated lane density over a defined region of interest with ImageJ/Fiji Tools (Belasco & Brawerman, 2012; Chen et al, 2008; Villa et al, 2021).…”
Section: Methodsmentioning
confidence: 99%